Stable Super‐Resolution Imaging of Lipid Droplet Dynamics through a Buffer Strategy with a Hydrogen‐Bond Sensitive Fluorogenic Probe. (18th October 2021) - Chen, Jie; Wang, Chao; Liu, Wenjuan; Qiao, Qinglong; Qi, Huan; Zhou, Wei; Xu, Ning; Li, Jin; Piao, Hailong; Tan, Davin; Liu, Xiaogang; Xu, Zhaochao
Abstract: Although super‐resolution imaging offers an opportunity to visualize cellular structures and organelles at the nanoscale level, cellular heterogeneity and unpredictability still pose a significant challenge in the dynamic imaging of live cells. It is thus vital to develop better‐performing and more photostable probes for long‐term super‐resolution imaging. Herein, we report a probe, LD‐FG, for imaging lipid droplet (LD) dynamics using structured illumination microscopy (SIM). LD‐FG allows wash‐free imaging of LDs, owing to a hydrogen‐bond sensitive fluorogenic response. The replacement of photobleached LD‐FG by intact probe molecules outside the LDs ensures the long‐time stability of the fluorescence imaging. With this buffering fluorogenic probe, fast and unpredictable dynamic processes of LDs can be visualized. Using this probe, two LD coalescence modes were discovered. The dynamic imaging also allowed us to propose a new model of LD maturation during adipocyte differentiation, i.e., a fast LD coalescence followed by a slow ripening step. The excellent performance of LD‐FG makes the buffer strategy an effective method for designing fluorescent probes for cell dynamic imaging. Abstract : We report a probe, LD‐FG, for imaging lipid droplet (LD) dynamics by using structure illumination microscopy. LD‐FG allows wash‐free imaging of LDs, owing to a hydrogen‐bond sensitive fluorogenic response. The replacement of photobleached LD‐FG with fresh probe molecules from outside the LDs ensures the long‐term stability of the imaging. With this buffering fluorogenic probe, fast and unpredictable dynamic processes of LDs can be visualized.